Lyz2-Cre-Mediated Genetic Deletion of Septin7 Reveals a Role of Septins in Macrophage Cytokinesis and Kras-Driven Tumorigenesis - Menon, Manoj B.; Yakovleva, Tatiana; Ronkina, Natalia; Suwandi, Abdulhadi; Odak, Ivan; Dhamija, Sonam; Sandrock, Inga; Hansmann, Florian; Baumgärtner, Wolfgang; Förster, Reinhold; Kotlyarov, Alexey; Gaestel, Matthias (Frontiers in Cell and Developmental Biology, 2022)
By crossing septin7-floxed mice with Lyz2-Cre mice carrying the Cre recombinase inserted in the Lysozyme-M (Lyz2) gene locus we aimed the specific deletion of septin7 in myeloid cells, such as monocytes, macrophages and granulocytes. Septin7flox/flox:Lyz2-Cre mice show no alterations in the myeloid compartment. Septin7-deleted macrophages (BMDMs) were isolated and analyzed. The lack of Septin7 expression was confirmed and a constitutive double-nucleation was detected in Septin7-deficient BMDMs indicating a defect in macrophage cytokinesis. However, phagocytic function of macrophages as judged by uptake of labelled E. coli particles and LPS-stimulated macrophage activation as judged by induction of TNF mRNA expression and TNF secretion were not compromised. In addition to myeloid cells, Lyz2-Cre is also active in type II pneumocytes (AT2 cells). We monitored lung adenocarcinoma formation in these mice by crossing them with the conditional knock-in Kras-LSL-G12D allele. Interestingly, we found that control mice without septin7 depletion die after 3–5 weeks, while the Septin7-deficient animals survived 11 weeks or even longer. Control mice sacrificed in the age of 4 weeks display a bronchiolo-alveolar hyperplasia with multiple adenomas, whereas the Septin7-deficient animals of the same age are normal or show only a weak multifocal brochiolo-alveolar hyperplasia. Our findings indicate an essential role of Septin7 in macrophage cytokinesis but not in macrophage function. Furthermore, septin7 seems absolutely essential for oncogenic Kras-driven lung tumorigenesis making it a potential target for anti-tumor interventions.